THE ARCHITECTURE OF THE OLD KISLOVODSK, TOURIST ROUTE - I. V. Lihodedova (Современная наука и инновации, 2022)
The article reveals the historical and architectural heritage of the world famous city-resort of Kislovodsk. A brief historical overview of the peculiar architecture monuments of the old town is represented. The description of structures for various purposes is given. The described buildings are widely known due to the fact that there were famous compatriots: A. S. Pushkin, Tolstoy, Lermontov etc.